2007
DOI: 10.1634/stemcells.2007-0296
|View full text |Cite
|
Sign up to set email alerts
|

Putative Role of Hyaluronan and Its Related Genes,HAS2andRHAMM, in Human Early Preimplantation Embryogenesis and Embryonic Stem Cell Characterization

Abstract: Human embryonic stem cells (hESC) promise tremendous potential as a developmental and cell therapeutic tool. The combined effort of stimulatory and inhibitory signals regulating gene expression, which drives the tissue differentiation and morphogenetic processes during early embryogenesis, is still very poorly understood. With the scarcity of availability of human embryos for research, hESC can be used as an alternative source to study the early human embryogenesis. Hyaluronan (HA), a simple hydrating sugar, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 74 publications
4
53
0
Order By: Relevance
“…Because CD44 is a major HA receptor, it provides a physical linkage between matrix HA and various transcription factors that regulate tumor cell functions through distinct signaling pathways (30,42). In fact, both HA and CD44 have been shown to be involved in self-renewal and differentiation of human embryonic stem cells (31,32). In this study, we observed that HA treatment promotes sphere formation (cell-cell adhesion), self-renewal/growth, and differentiation (e.g.…”
Section: Discussionmentioning
confidence: 71%
“…Because CD44 is a major HA receptor, it provides a physical linkage between matrix HA and various transcription factors that regulate tumor cell functions through distinct signaling pathways (30,42). In fact, both HA and CD44 have been shown to be involved in self-renewal and differentiation of human embryonic stem cells (31,32). In this study, we observed that HA treatment promotes sphere formation (cell-cell adhesion), self-renewal/growth, and differentiation (e.g.…”
Section: Discussionmentioning
confidence: 71%
“…Because CD44 is an HA receptor, it provides a physical linkage between matrix HA and various transcription factors that regulate tumor cell functions through distinct signaling pathways (5,28,29). In fact, both HA and CD44 have been shown to be involved in self-renewal and differentiation of human ESC (64,65). In this study, we observed that the HA-CD44 interaction promotes sphere formation (cell-cell adhesion), self-renewal/growth, and clonal formation in a highly tumorigenic CD44v3 high ALDH1 high tumor cell population (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our knowledge about mammalian development, which is definitely important to correctly manage the basic strategies required for the therapeutic use of ES cells or iPS cells, is restricted to mice. Thus, hESCs are expected to substitute for the human fetus, at least in part, to unravel the mystery of human-specific developmental mechanisms (Cauffman et al, 2006(Cauffman et al, , 2009Choudhary et al, 2007;Dvash et al, 2004Dvash et al, , 2006Gjerstorff et al, 2008;Pera and Trounson, 2004;Rugg-Gunn et al, 2005). Even restricted to the ocular cells or tissues, only cultured cornea cell sheets induced from epithelial stem cells have been used for therapy (Nozaki et al, 2008;Sekiyama et al, 2006), and many induced cell types including those of retina and retinal pigmented epithelium have been used only in animal models (Kubota et al, 2006;MacLaren et al, 2006;Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%